Trial‐based economic evaluation of mindfulness‐based cognitive therapy compared to treatment as usual for bipolar disorder - Wijnen, Ben; Jansen, Maud; Velthoven, Annelieke; Hanssen, Imke; Huijbers, Marloes; Evers, Silvia; Speckens, Anne (International journal of methods in psychiatric research, 2024)
Objective Aim of this study was to assess the cost‐effectiveness and cost‐utility of mindfulness‐based cognitive therapy (MBCT) and treatment as usual (TAU) compared to TAU alone in adults with Bipolar disorder (BD). Methods An economic evaluation with a time horizon of 15 months was conducted from a societal perspective. Outcomes were expressed in costs per quality adjusted life years (QALYs) and costs per responder using the inventory of depressive symptomatology clinician rating score. Results People with BD (N = 144) were included in this study. From a societal perspective, the difference of total costs between MBCT + TAU and TAU was €615, with lower costs in the MBCT + TAU group. Only healthcare costs differed significantly between the two groups. A small difference in QALYs in favor of MBCT + TAU was found combined with lower costs (−€836; baseline adjusted) for MBCT + TAU compared to TAU, resulting in a dominant incremental cost‐utility ratio. The probability that the MBCT + TAU was cost‐effective was 65%. All sensitivity analyses attested to the robustness of the base case analyses. Conclusion Concludingly, MBCT + TAU seems to be cost‐effective compared to TAU alone, indicated by a small or neglectable difference in effect, in favor of MBCT + TAU, while resulting in lower costs.